2011
DOI: 10.1093/jaoac/94.1.9
|View full text |Cite
|
Sign up to set email alerts
|

RP-HPLC Analysis of Phenolic Acids of Selected Central European Carex L. (Cyperaceae) Species and Its Implication for Taxonomy

Abstract: Eighteen species belonging to the Carex genus were checked for the presence and the amount of eight phenolic acids (p-hydroxybenzoic, vanillic, caffeic, syringic, protocatechuic, p-coumaric, sinapic, and ferulic) by means of HPLC. Both the free and bonded phenolic acids were analyzed. The majority of the analyzed acids occurred in the studied species in relatively high amounts. The highest concentrations found were caffeic acid and p-coumaric acid, for which the detected levels were negatively correlated. A ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…While in both cases the predominant signals belong to p-coumaric acid at 830 cm −1 in FTIR and 1605 cm −1 in FT-Raman, grasses have additional signals associated with ferulic acid at 850 and 1605 cm −1 in FTIR and FT-Raman respectively, while sedges have signals associated with sinapic acid at 815 and 1595 cm −1 in FTIR and FT-Raman respectively. This is in accordance with phenylpropanoid studies of plant vegetative tissues which have shown that grass cell walls are characterized by ferulic and p-coumaric acids, while sedges contain sinapic and p-coumaric acids (Bogucka-Kocka et al, 2011;De Oliveira et al, 2015). Sinapic acid is rarely detected in plant tissues, and it has been hypothesized that its presence in tissues of a number of Carex species can be associated with the humidity of plants' habitats (Bogucka-Kocka et al, 2011).…”
Section: Chemical Composition Of Phenylpropanoids In Pollen Grain Wallsupporting
confidence: 87%
See 1 more Smart Citation
“…While in both cases the predominant signals belong to p-coumaric acid at 830 cm −1 in FTIR and 1605 cm −1 in FT-Raman, grasses have additional signals associated with ferulic acid at 850 and 1605 cm −1 in FTIR and FT-Raman respectively, while sedges have signals associated with sinapic acid at 815 and 1595 cm −1 in FTIR and FT-Raman respectively. This is in accordance with phenylpropanoid studies of plant vegetative tissues which have shown that grass cell walls are characterized by ferulic and p-coumaric acids, while sedges contain sinapic and p-coumaric acids (Bogucka-Kocka et al, 2011;De Oliveira et al, 2015). Sinapic acid is rarely detected in plant tissues, and it has been hypothesized that its presence in tissues of a number of Carex species can be associated with the humidity of plants' habitats (Bogucka-Kocka et al, 2011).…”
Section: Chemical Composition Of Phenylpropanoids In Pollen Grain Wallsupporting
confidence: 87%
“…This is in accordance with phenylpropanoid studies of plant vegetative tissues which have shown that grass cell walls are characterized by ferulic and p-coumaric acids, while sedges contain sinapic and p-coumaric acids (Bogucka-Kocka et al, 2011;De Oliveira et al, 2015). Sinapic acid is rarely detected in plant tissues, and it has been hypothesized that its presence in tissues of a number of Carex species can be associated with the humidity of plants' habitats (Bogucka-Kocka et al, 2011).…”
Section: Chemical Composition Of Phenylpropanoids In Pollen Grain Wallsupporting
confidence: 87%
“…These species may be a good source of free radicals (Kilani-Jaziri 2011). The results of the present study showed similar findings as analyzed by Bogucka-Kocka et al (2011) that the content of the studied polyphenolic compounds varied in the investigated species (Table 4). This is probably due to the non-specificity of these polyphenolic compounds among the species of Carex, Cyperaceae.…”
Section: Discussionsupporting
confidence: 89%
“…The genus Carex has several infrageneric taxa like sub-genera and sections, mostly identified based on morphological characters and genetic characters (Hendrichs et al 2004) and very rarely on the basis of phytochemicals. Thus, chemotaxonomic aspects are rare in Cyperaceae (Harborne 1971;Bogucka-Kocka et al 2011). The therapeutic evaluation of the genus is also very rare (Gonza ĺez-Sarrias et al have not yet even been screened for their phytochemical constituents including polyphenolics, which could be a good source of the bioactive components and also be important species in therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation